Is bovine density and ownership associated with human tuberculosis in India? - Katriina Willgert; Susie da Silva; Ruoran Li; Premanshu Dandapat; Maroudam Veerasami; Hindol Maity; Mohan Papanna; Sreenidhi Srinivasan; James L N Wood; Vivek Kapur; Andrew J K Conlan (PLoS ONE, 2023)
Zoonotic tuberculosis in humans is caused by infection with bacteria of the Mycobacterium tuberculosis complex acquired from animals, most commonly cattle. India has the highest burden of human tuberculosis in the world and any zoonotic risk posed by tuberculosis in bovines needs to be managed at the source of infection as a part of efforts to end human tuberculosis. Zoonotic tuberculosis in humans can be severe and is clinically indistinguishable from non-zoonotic tuberculosis. As a consequence, zoonotic tuberculosis remains under-recognised and the significance of its contribution to human tuberculosis is poorly understood. This study aimed to explore any association between bovine density, bovine ownership, and human tuberculosis reporting in India using self-reported tuberculosis data in households and officially reported tuberculosis cases while controlling for common confounders for human tuberculosis. We find an association between human tuberculosis reporting, bovine density and bovine ownership in India. Buffalo density was significantly associated with an increased risk of self-reported tuberculosis in households (odds ratio (OR) = 1.23 (95% credible interval (CI): 1.10-1.39) at household level; incidence rate ratio (IRR) = 1.17 (95% CI: 1.04-1.33) at district level), while cattle density (OR = 0.80, 95% CI: 0.71-0.89; IRR = 0.78, 95% CI: 0.70-0.87) and ownership of bovines in households (OR = 0.94, 95% CI: 0.9-0.99; IRR = 0.67, 95% CI: 0.57-0.79) had a protective association with tuberculosis reporting. It is unclear whether this relates to differences in tuberculosis transmission dynamics, or perhaps an association between bovines and other unexplored confounders for tuberculosis reporting in humans. Our study highlights a need for structured surveillance to estimate the prevalence of tuberculosis in cattle and buffaloes, characterisation of Mycobacterium tuberculosis complex species present in bovines and transmission analyses at the human-animal interface to better assess the burden and risk pathways of zoonotic tuberculosis in India.